Identification of Micro Ribonucleic Acids and Their Targets in Response to Plasmodiophora brassicae Infection in Brassica napus - Li, Qian; Shah, Nadil; Zhou, Xueqing; Wang, Huiying; Yu, Wenlin; Luo, Jiajie; Liu, Yajun; Li, Genze; Liu, Chao; Zhang, Chunyu; Chen, Peng (Frontiers in Plant Science, 2021)
Clubroot disease caused by the soil-borne pathogen Plasmodiophora brassicae War (P. brassicae), is one of the world’s oldest and most destructive disease of Brassica species and cruciferous crops. Plant microRNAs (miRNAs) play important regulatory roles in a number of developmental processes. Although a number of reports have focused on the role of plant miRNAs in plant–microbe interactions, relatively few studies specifically addressed the specific functions for miRNAs in response to P. brassicae. This work investigated the roles of miRNAs and their targets during P. brassicae infection in two B. napus near-isogenic lines (NILs) of clubroot-resistant (409R) and clubroot-susceptible (409S). sRNA-seq and degradome-seq were applied on root samples from 409R or 409S before or 20 days after P. brassicae inoculation. We identified 48 conserved and 72 novel miRNAs from sRNA-seq, among which 18 miRNAs were significantly differentially expressed in the resistant materials after P. brassicae inoculation in root when compared to uninfected root, while only 1 miRNA was differentially expressed in the susceptible materials. Analysis of the degradome-seq identified 938 miRNA target transcripts, and most of them were transcription factors, enzymes and proteins involved in multiple biological processes, which most significantly enriched in plant hormone signal transduction pathway. Eight different degradation pathways between the clubroot-resistant line and clubroot-susceptible line in response to P. brassicae infection were identified, for example fatty acid related-pathways. Combining with published transcriptome data, we totally identified 6 antagonistic miRNA-target pairs in resistant NIL 409R in response to P. brassicae infection, which were involved in root development, hypersensitive (HR) cell death and chloroplast metabolic synthesis related-pathways. Our data reveals that P. brassicae infection results in fundamental changes on miRNA pool and target transcripts, more interestingly, these responses are different between clubroot-resistant and -susceptible lines. The crosstalk between miRNAs and targets may shed light on possible mechanisms behind pathogen resistance upon P. brassicae infection.